Efficacy of nonsurgical periodontal therapy on glycaemic control in type II diabetic patients: a randomized controlled clinical trial - Telgi, Ravishankar Lingesha (Korean Academy of Periodontology, 2013)
PURPOSE: Diabetes and periodontal disease are two common diseases with high prevalence rates. Recent evidence has shown a bidirectional relationship between diabetes and periodontitis. The aim of this study was to investigate the effects of nonsurgical periodontal therapy on glycemic control in type 2 diabetes mellitus patients. METHODS: Sixty subjects aged 35-45 years with blood sugar controlled by oral hypoglycaemic agents were randomly divided equally among 3 groups: group A (scaling, mouthwash, and brushing), group B (mouthwash and brushing), and group C (brushing only). Glycated haemoglobin (HbA1c), fasting blood sugar (FBS), probing pocket depth (PPD), gingival index (GI), plaque index (PI), and the relevant drug history were recorded at baseline and after 3 months of intervention. Comparison of the mean difference among the variables was performed by parametric and nonparametric tests, which were further evaluated using multiple regression analysis. RESULTS: The mean differences between the PPD, FBS, HbA1c, GI, and PI in groups A and B were found to be statistically significant (P<0.001). Multiple regression analysis in group A showed that out of all the independent variables, GI and frequency of drug administration independently (b=0.3761 and b=0.598) showed a significantly greater impact on HbA1c (R(2)=0.832, P<0.05). CONCLUSIONS: Nonsurgical periodontal therapy can effectively decrease HbA1c levels in type 2 diabetes mellitus patients on medication.